http://fsu.ua/index.php/en/2017/2-2017-40/2017-02-099-113-kononenko - O. Baturevich (Ribogospodarsʹka Nauka Ukraïni, 2017)
Purpose.To describe the basic physical-chemical and biological properties of certain minerals of volcanic origin, which are deposited in Ukraine.To examine and make a comparative assessment of their chemical composition and biological properties including zeolite, bentonite and saponite. To summarize performance data on the effectiveness of their use in animal, poultry and fish feed as a feed additive.